PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN DATAR SEGITIGA SISWA KELAS VII SMP NEGERI 2 KOTABARU TAHUN PELAJARAN 2016/2017 - Muhammad Ali; Usman DP (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
This study aims to: (1) Knowing the student of Class VII learning outcomes SMP Negeri 2 Kotabaru using cooperative learning model The Power of Two, if viewed from the initial capability. (2) Know the difference between student learning outcomes in the classroom are applied cooperative learning model The Power of Two with the class applied direct instructional model (3) Knowing the Class VII student response SMP Negeri 2 Kotabaru to learning mathematics using cooperative learning model The Power of Two. The results of this study are expected to be useful for: (1) Students, can enhance the activity in the learning of mathematics. (2) The teacher, as a motivation to develop creativity and provide insight into the learning model. (3) Schools, as reference material for the library. The method used was experimental studies included in the quasi experiment. The data collected with use of the test, questionnaire, and documentation. The results showed improving student learning outcomes in the amount of 28.1% when viewed from the ability to start. Students also responded to agree to the study of mathematics by cooperative learning model The Power of Two. Keywords: Cooperative Learning Model The Power of Two, Learning Outcomes.